2004
DOI: 10.1158/1078-0432.ccr-03-0703
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responses in Women with Human Papillomavirus Type 16 (HPV-16)-Associated Anogenital Intraepithelial Neoplasia Induced by Heterologous Prime-Boost HPV-16 Oncogene Vaccination

Abstract: Purpose:The purpose is to study the immunogenicity of heterologous prime-boost human papillomavirus (HPV) oncogene vaccination in patients with anogenital intraepithelial neoplasia (AGIN).Experimental Design: Twenty-nine women with highgrade AGIN received three i.m. doses of TA-CIN (HPV-16 L2/E6/E7 protein) at four weekly intervals followed by a single dermal scarification of vaccinia HPV-16/18 E6/E7 and were followed up for 12 weeks. Immunity to HPV-16 was assessed by lymphoproliferation, IFN-␥ enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 10 publications
3
102
2
1
Order By: Relevance
“…In summary, we have shown that ELISPOT assays of IFN-g release are capable of revealing T-cell reactivities to HPV16 antigens in women with cervical dysplasia and can be used to establish the spectrum of T-cell responses induced during natural infection. The ELISPOT assay is becoming established as a good method for charting HPV-specific immunity, both during natural infection and following vaccination (van der Burg et al, 2001;de Jong et al, 2002de Jong et al, , 2004Steele et al, 2002;Baldwin et al, 2003;Welters et al, 2003;Smith et al, 2004;Smyth et al, 2004). Setting the vaccination studies aside, there are differences between the conclusions drawn from the studies looking at natural immunity and those obtained in this study.…”
Section: Seropositivity Is Related To Positive T-cell Reactivitymentioning
confidence: 78%
“…In summary, we have shown that ELISPOT assays of IFN-g release are capable of revealing T-cell reactivities to HPV16 antigens in women with cervical dysplasia and can be used to establish the spectrum of T-cell responses induced during natural infection. The ELISPOT assay is becoming established as a good method for charting HPV-specific immunity, both during natural infection and following vaccination (van der Burg et al, 2001;de Jong et al, 2002de Jong et al, , 2004Steele et al, 2002;Baldwin et al, 2003;Welters et al, 2003;Smith et al, 2004;Smyth et al, 2004). Setting the vaccination studies aside, there are differences between the conclusions drawn from the studies looking at natural immunity and those obtained in this study.…”
Section: Seropositivity Is Related To Positive T-cell Reactivitymentioning
confidence: 78%
“…9,10 Studies on the HPV18-specific T-cell immune response are scarce and limited to the identification of potential CTL epitopes 11,12 or vaccine-induced immunity. 13,14 Our studies on the presence and type of HPV16 E2-, E6-and E7-specific T-cell immunity in healthy subjects suggested that type 1 T-helper cell reactivity against HPV16 E2 and E6, which was present in the great majority of healthy individuals, played a role in protection to progressive infection. [15][16][17][18] In view of the behavioral differences between HPV16 and HPV18, in particular that in duration of viral persistence, we have analyzed the type 1 T-helper cell response to HPV18 oncoproteins E6 and E7 in healthy subjects and compared this with T-cell reactivity in HPV18-positive cancer patients.…”
mentioning
confidence: 84%
“…Based on our previous reports, antigen-specific Tcell frequencies were considered to be increased compared to nonresponders when specific T-cell frequencies were 1/10,000. 27,28 HPV16 VLP ELISA For the detection of HPV16-specific antibodies in serum, we used an ELISA method previously described by Kirnbauer et al 29 Each serum sample was diluted 30 times and tested for reactivity against HPV16 virus-like particles (VLP, baculovirus-expressed capsids comprising the L1 protein) and against bovine papillomavirus (BPV) capsids, the latter disrupted by treatment with 0.1 M carbonate buffer to serve as a negative control. Both VLP and BPV were kindly provided by Prof. Dr. J. Dillner (LUNDS University, Sweden).…”
Section: Antigensmentioning
confidence: 99%
“…Based on our previous reports, responses were considered positive if peptide pool-specific T-cell frequencies were 10/100,000 PBMC. 27,28 These values are indicated in bold. Values below this threshold are shown in italics.…”
Section: Antigensmentioning
confidence: 99%